Anaemia and red blood cell transfusion in women with placenta accreta spectrum: an analysis of 38,060 cases - Jan Andreas Kloka; Benjamin Friedrichson; Thomas Jasny; Lea Valeska Blum; Suma Choorapoikayil; Oliver Old; Kai Zacharowski; Vanessa Neef (Scientific Reports, 2024)
Abstract Placenta accreta spectrum (PAS) has become a significant life-threatening issue due to its increased incidence and associated morbidity and mortality. Pregnancy is often associated with states of anaemia, and severe maternal haemorrhage represents a major risk factor for red blood cell (RBC) transfusion. The present study retrospectively analyzed the prevalence of anaemia, transfusion requirements and outcome in women with PAS. Using data from the German Statistical Office pregnant patients with deliveries hospitalized between January 2012 and December 2021 were included. Primary outcome was the prevalence of anemia and administration of RBCs. Secondary outcome were complications in women with PAS who received RBC transfusion. In total 6,493,606 pregnant women were analyzed, of which 38,060 (0.59%) were diagnosed with PAS. The rate of anaemia during pregnancy (60.36 vs. 23.25%; p < 0.0001), postpartum haemorrhage (47.08 vs. 4.41%; p < 0.0001) and RBC transfusion rate (14.68% vs. 0.72%; p < 0.0001) were higher in women with PAS compared to women without PAS. Women with PAS who had bleeding and transfusion experienced significantly more peripartum complications than those who did not. A multiple logistic regression revealed that the probability for RBC transfusion in all pregnant women was positively associated with anaemia (OR 21.96 (95% CI 21.36–22.58)). In women with PAS, RBC transfusion was positively associated with the presence of renal failure (OR 11.27 (95% CI 9.35–13.57)) and congestive heart failure (OR 6.02 (95% CI (5.2–7.07)). Early anaemia management prior to delivery as well as blood conservation strategies are crucial in women diagnosed with PAS.